“Whirlpools” and “Safe Harbors” in the Dynamics of Industrial Specialization in Russian Regions - Evgeniy Kutsenko; Yaroslav Eferin (Foresight and STI Governance)
This article analyzes sectors of specialization and sectoral dynamics in the regions of the Russian Federation from 2005 to 2015. The study is based on the methodology of the European Cluster Observatory in the 2016 edition as revised by the authors. It proposes a typology of regions depending on the number of specialization industries and the depth of sectoral development: agglomeration, diversification, specialization, and differentiation. Four types of specializations are identified based on the depth of their development and distribution among Russian regions: national leadership, distribution, concentration, and niche development. The authors implemented an approach to study regions through alternative scenarios of sectoral development over a ten-year period: occurrence, strengthening, extinction, and disappearance. The study identifies various structural models that combine the implementation of the described scenarios in relation to various specializations within a particular region. It is shown that the scale and intensity of structural changes largely depends on the region’s proximity to millionaire cities but does not always directly affect economic growth rates. The authors introduce the concepts of “sinkholes”, “streams”, and “safe harbors”, which describe the types of regions with a different type of structural changes that occur depending on the presence or proximity of the millionaire city.